Tindak Tutur Tokoh dalam Novel Negeri 5 Menara Karya Ahmad Fuadi - Nursafitri, Intan Suci; Asri, Yasnur (Indonesian and Regional Language and Literature Department, Universitas Negeri Padang, 2023)
This research is motivated by the problem of how locutionary, illocutionary, and perlocutionary speech acts are in the discourse of the novel Negeri 5 Menara by Ahmad Fuadi. The purpose of this study is to describe the locutionary, illocutionary, and perlocutionary speech acts in the discourse of the novel Negeri 5 Menara by Ahmad Fuadi. This research is included in the type of qualitative research that uses descriptive methods. The data collection technique in this research is a document review study, with the following steps. First, read and understand the novel Negeri 5 Menara by Ahmad Fuadi, second, identify words that contain speech acts in the novel Negeri 5 Menara by Ahmad Fuad, and third, take an inventory of data containing speech acts in the novel Negeri 5 Menara by Ahmad Fuadi. The data analysis technique used is pragmatic analysis. The results of this study indicate that there are locutionary, illocutionary, and perlocutionary speech acts in the discourse of the novel Negeri 5 Menara by Ahmad Fuadi.